EVALUATION ON SUMBER SENENG NATURAL PARK, REMBANG AS TOURISM OBJECT USING ADO-ODTWA ANALYSIS - Susanti, Anityas Dian; Mandaka, Mutiawati (architecture department, Engineering faculty, Universitas Diponegoro, 2019)
Tourism has proven as economic generator in several local districts in Indonesia. Natural resources have significant factors in accelerating the tourism developments. Sumber seneng in Rembang county is an example of the natural resource based tourism district. However the development of Sumber seneng park is still on going process related to the district potential’s study. ADO-ODTWA (Analisis Daerah Operasi Obyek dan Daya Tarik Wisata Alam) is an analysis for tourist attraction from Indonesia Forest and Natural Conservation Agency. This research was part of the study to evaluate Sumber seneng park as object tourism case using ADO-ODTWA analysis. This study performed literature study to arrange the evaluation sheet, site observation based on the ADO-ODTWA evaluation’s results as case study. The result of this study shown detail steps to evaluate tourism object using ADO ODTWA and mentioned that Sumber Seneng Natural Park has potentials to be tourism object and need more development to optimize it.